Effectiveness of Read Aloud in Improving Pre-Reading Skills in Children Aged 4-5 Years at The RA Darul Falah Ketanggen - Naili Rohmah; Fitriani, nabila nur (Universitas Negeri Semarang, 2024)
Therefore, it is very important to develop and educate children so that children can improve their English skills and be able to understand English well. Reading is a basic skill that can help children to succeed in academic and non-academic fields in the future. The purpose of this study was to test the effectiveness of reading aloud in improving children's pre-reading ability, as well as applying the strategy of learning to read aloud in education in RA Darul Falah Ketanggen. In this study, the research uses pre experimental design research method in which the research will involve experimental groups and intervene at the time of research in the form of one group pretest post test design. The location of the study was conducted in Ra Darul Falah Ketanggen. Sampling using non-Probability Sampling with purposive sampling technique based on Yamane formula. The number of samples in the study was 28 respondents. Data collection is done by using questionnaires or questionnaires. The data were analyzed using Shapiro-Wilk normality test, t test, and N-Gain test. The results of statistical calculations using SPSS, show that reading aloud has an impact on the pre-reading ability of children aged 4-5 years with a black t value of 63.95 > t table 0.374. And read aloud effectively in improving children's pre-reading ability with N-Gain test results from this study is 77%. And there was an increase of 51.68 points in the posttest value compared to the pretest value.